ECONOMIC ANALYSIS OF THE RIOBAMBA CANTON IN ECUADOR DURING THE “CORREATO” - Vives Sarmiento, Jessenia Valeria (2021)
The economic and political evolution of Ecuador, during the period 2007-2017, converges around the government of Rafael Correa, known as the “Correato”. This article reviews the ideological context of Socialism of the xxi century, the economic context of Correato, and the impact of economic policies in the canton of Riobamba. The economic growth of Riobamba was based on construction, transportation, and manufacturing. The policies implemented during the “Correato” led to an increase in public debt to sustain economicgrowth. However, starting in 2015, growth stops, and economic and social variables beginto recede.